Evaluación de clones de Pinot noir en la Norpatagonia - Gallina, M. (2023)
Fil: Gallina, M. Instituto Nacional de Tecnología Agropecuaria. Estación Experimental Agropecuaria Alto Valle (INTA); Argentina